Hubungan Antara Cognitive Reappraisal, Expressive Suppression, dan Self-Compassion Terhadap Psychological Well-Being Siswa SMP - Rifa Aulia Zahro; Zakki Nurul Amin (Scidacplus, 2026)
Adolescence is a developmental phase characterized by various biological, emotional, social, and cognitive changes. The ability to manage emotions and self-compassion are factors that can support adolescent psychological well-being. This study aimed to examine the relationship of cognitive reappraisal, expressive suppression, and self-compassion with the psychological well-being of junior high school students. The study employed a quantitative approach with a correlational design. The sample consisted of 123 junior high school students selected through purposive sampling. The instruments used were the Emotion Regulation Questionnaire (ERQ), the Self-Compassion Scale, and the Psychological Well-Being Scale. Data were analyzed using multiple linear regression. The results showed that cognitive reappraisal and self-compassion were positively and significantly associated with psychological well-being, whereas expressive suppression was negatively and significantly associated with psychological well-being. Furthermore, these three variables simultaneously contributed significantly to the psychological well-being of junior high school students. These findings suggest that adaptive emotion regulation and self-compassion play important roles in enhancing adolescents’ psychological well-being.